ð˜›ð˜¶ð˜£ð˜ªð˜¹ð˜¢ð˜£ð˜¢ ð˜µð˜¶ð˜¹ð˜¢ð˜¶ð˜¢ N. G. N. SP., A SUSPECTED PARASITIC NEMATODE OF SOYBEAN ROOTS (APORCELAIMIDAE) - Monteiro, Ailton Rocha; Lordello, Luiz Gonzaga E. (REVISTA DE AGRICULTURA, 2020)
ð˜›ð˜¶ð˜£ð˜ªð˜¹ð˜¢ð˜£ð˜¢ ð˜µð˜¶ð˜¹ð˜¢ð˜¶ð˜¢ N. G. N. SP., A SUSPECTED PARASITIC NEMATODE OF SOYBEAN ROOTS (APORCELAIMIDAE)